THE RELATIONSHIP OF SCENARIO QUALITY WITH THE EFFECTIVENESS OF SEVEN JUMPS PROBLEM-BASED LEARNING DISCUSSION ON MEDICAL STUDENTS OF MULAWARMAN UNIVERSITY - Gusti Ferri Sandaria; Sulistiawati Sulistiawati; Cicih Bhakti Purnamasari (Jurnal Ilmu Kesehatan, 2021)
Problem-based learning is a learning method which applies scenario arranged thoroughly according to specific themes and performed through group discussion. The effectiveness of problem-based learning determines the success of students’ learning. This study aims to find the relationship between scenario quality and the effectiveness of problem-based learning seven jumps discussion among medical students of Mulawarman University. This observational analytic study applied cross sectional approach. The respondents of this study were medical students of Mulawarman University which were selected through simple random sampling technique. The data analysis methods were descriptive data analysis and analytic data analysis using Pearson test. There were 202 respondents fulfilling both inclusive and exclusive criteria with 18 – 22 age range. The male respondents were 50 (24.8%) and the female respondents were 152 (75.2%). Each respondent filled in questionnaires twice to evaluate different scenario. A total of 404 data were obtained from 202 respondents. The finding revealed that there was a correlation between scenario quality and problem-based learning seven jumps discussion with p value = 0.000. In conclusion, scenario quality had a relationship with the effectiveness of problem-based learning seven jumps discussion among medical students of Mulawarman University.